PENGEMBANGAN MODUL PEMBELAJARAN IPA (SCIENCE) BERBASIS KARAKTER UNTUK SISWA TK DI SEKOLAH CINTA KASIH SORONG - Stefany Margareta Martono (SOSCIED, 2020)
The development of a Character-Based Science Learning Module for Kindergarten students at Cinta Kasih Sorong School is a module development that can help teachers in providing science (Science) material as well as training skills and encouraging student development intellectually and training students to have a characterist attitude. The purpose of this research is the development of modules to make interesting learning so that students can develop cognitive independently through science learning combined with character-based methods. The module development design of this study uses the research and development method or "research and development" (R & D) following the stages of development research according to Brog and Gall. The data analysis used was an analysis of the feasibility of the module by taking the average value data of students during the learning process and interpreting it qualitatively by anecdotal assessment by the teacher. The results of the study the average score for class A was 73,100 and class B was 72,250. Based on the average score taken during the learning process, it proves that the two classes have almost the same value. This proves that the modified module can increase students' imagination and understanding. The characters that are assessed by anecdotal notes are cooperation, independence, responsibility, mutual help, order and discipline. The conclusion of the research results is that the development of a Character-Based Science (Science) Learning Module developed through this research and development is suitable for use as a module in the Science learning process for Kindergarten students at Cinta Kasih Sorong School. Keywords: development, module, science, character.